AHP Implementation in Best Lecturer Selection at FKIP UNIVED - Bambang Supperianto; Magdalena Sundari (Jurnal Media Computer Science, 2026)
The determination of the best lecturer is a critical strategic process in enhancing institutional quality assurance in higher education. Conventional evaluation approaches are frequently characterized by subjectivity and the absence of structured multi-criteria weighting mechanisms, leading to potential inconsistencies in decision outcomes. This study proposes an Analytical Hierarchy Process (AHP)-based Decision Support System (DSS) to improve the objectivity and reliability of best lecturer selection at the Faculty of Teacher Training and Education, Universitas Dehasen Bengkulu. AHP is employed to structure the decision hierarchy and derive priority weights through pairwise comparison matrices, ensuring consistency in multi-criteria evaluation. The assessment framework incorporates pedagogical competence, professional competence, personality, social competence, and academic performance within the tridharma of higher education. Empirical data were collected through structured questionnaires and institutional performance records. The consistency ratio (CR) of all comparison matrices met the acceptable threshold (CR < 0.1), indicating reliable judgment consistency. The proposed model enhances transparency by quantifying subjective judgments into measurable priority scores and generating a systematic ranking of lecturers. This study contributes methodologically by integrating hierarchical decision modeling with institutional performance evaluation, offering a replicable framework for academic quality assessment. The findings demonstrate that the AHP-based DSS provides a robust and accountable decision-making tool for strategic lecturer evaluation in higher education institutions.